A multi-analytical approach to investigate the motivations of sustainable green technology in the banking industry: Do gender and age matter? - Mohamed Bouteraa; Meshari Al-Daihani; Rudy Ansar; Elhachemi Tamma; Abderrahmane Baddou; Lim, Ming Fook (IGI Global, 2023)
Sustainability has become the global need for survival in all scopes due to financial development's side effects that have resulted in environmental destruction. The world leaders have proposed green banking (GB) to reduce carbon footprints from banking operations by promoting paperless financial services based on technology. However, the customers' adoption of GB remains unsatisfactory in the UAE. This study attempts to investigate the determinants of consumers' intention adoption of GB. An exploratory sequential mixed-method approach is employed. The qualitative analysis identified six new challenges facing customers' intention adoption of GB: customer awareness, personal innovativeness, bank reputation, security and privacy, system quality, and government support. The qualitative findings are mostly confirmed by quantitative study whereby awareness, personal innovativeness, system quality, and bank reputation significantly impact customers' intention to adopt GB. The study also revealed the insignificant moderating impact of gender and age in most proposed relationships.